Plant hormone effects on isoprene emission from tropical tree in Ficus septica. (14th February 2019) - Parveen, Shahanaz; Iqbal, Md. Asif; Mutanda, Ishmael; Rashid, Md. Harun‐Ur‐; Inafuku, Masashi; Oku, Hirosuke
Abstract: Plant hormones and the circadian rhythm have been implicated in coordinated control of isoprene emission in plants. To gain insights into the signalling networks, foliar application of plant hormones was conducted in a native emitter, Ficus septica . Spraying of 50 μM jasmonic acid (JA) gradually decreased isoprene emission by 88% compared with initial levels within 5 days, and emission increased after relief from JA application. We further explored the molecular regulatory mechanism of isoprene emission by analysing photosynthetic rate, gene expression of 2‐C‐methyl‐D‐erythrytol 4‐phosphate (MEP) pathway, hormone signalling and circadian rhythm processes, and metabolite pool sizes of MEP pathway. Results show that isoprene emission strongly correlated with isoprene synthase ( IspS ) gene expression and IspS protein levels over the period of JA treatment, indicating transcriptional and possible translational modulation of IspS by JA. Application of JA coordinately modulated genes in the auxin, cytokinin (CK), and circadian rhythm signal transduction pathways. Among the transcriptional factors analysed, MYC2 (JA) and LHY (circadian clock) negatively correlated with isoprene emission. Putative cis ‐elements predicted on IspS promoter (G‐box for MYC2 and circadian for LHY ) supports our proposal that isoprene emission is regulated by coordinated transcriptional modulation of IspS gene by phytohormone and circadian rhythm signalling. Abstract : Hormonal regulation effects on isoprene emission in the tropical plant Ficus septica . Among the five hormones: jasmonic acid (JA), abscisic acid, gibberelic acid, 3‐indole acetic acid, and salicylic acid exogenously sprayed on the leaves of the tropical tree F . septica, JA showed the strongest modulation of isoprene emission. Gene expression analysis suggests JA modulates IspS gene through the bHLH transcription factor MYC2 that directly binds to the G‐box on IspS promoter.